2014
DOI: 10.1111/cfs.12142
|View full text |Cite
|
Sign up to set email alerts
|

What social workers do in performing child protection work: evidence from research into face‐to‐face practice

Abstract: A B S T R AC TLittle research has been done into what social workers do in everyday child protection practice. This paper outlines the broad findings from an ethnographic study of face-to-face encounters between social workers, children and families, especially on home visits. The social work practice was found to be deeply investigative. Children's bedrooms were routinely inspected and were the most common place where they were seen alone. A high proportion of children were not seen on their own because they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 21 publications
2
96
1
6
Order By: Relevance
“…Munro 2011;Nordlander 2006;Osmond 2001). The importance of building client-professional relationships in social work practice has been well documented in previous research (Broadhurst et al 2010;Ferguson 2014;McCracken & Marsh 2008; Van de Luitgaarden 2011). Nordlander's (2006) study on social worker's knowledge use in investigation work showed that once facts were established, social workers tended to choose interventions that had the capacity to lead to desirable results.…”
Section: Knowledge For Decision Making In Practicementioning
confidence: 78%
See 1 more Smart Citation
“…Munro 2011;Nordlander 2006;Osmond 2001). The importance of building client-professional relationships in social work practice has been well documented in previous research (Broadhurst et al 2010;Ferguson 2014;McCracken & Marsh 2008; Van de Luitgaarden 2011). Nordlander's (2006) study on social worker's knowledge use in investigation work showed that once facts were established, social workers tended to choose interventions that had the capacity to lead to desirable results.…”
Section: Knowledge For Decision Making In Practicementioning
confidence: 78%
“…Although there are exceptions (e.g. Ferguson 2014;Nordlander 2006;Osmond 2001;White 1997;, there is a paucity of studies on professionals' actual knowledge use.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…A recent ethnographic study of face-to-face encounters that social workers have with children and their families found that practitioners had varying levels of communication skills, playfulness and comfort with getting close to children. In those cases where practitioners did have these relational capacities, they were found to have developed deep and meaningful relationships but this was not consistent across practitioners (Ferguson, 2014). There is a drought of good literature in this area, and most social work educators have forgotten or lost interest in what they once knew, and never practice themselves.…”
Section: Moving Beyond Assessmentmentioning
confidence: 94%
“…Children and young people ordinarily understand the importance of the quality of worker-client relationships, which can take time to develop, compared to those that feel robotic and rushed (Ferguson, 2014). Ferguson (2014, p. 8) contrasted this latter style to the social worker who:…”
Section: Qualitative Researchmentioning
confidence: 99%